THE ROLE OF THE TEACHER IN SHAPING THE DISCIPLINARY CHARACTER OF UPPER-CLASS ELEMENTARY SCHOOL STUDENTS - Lisapaly, Grace; Kempa, Rudolf; Rumfot , Sumarni (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to describe the role of teachers in shaping the disciplinary character of upper elementary school students at SD Air Louw, located on Jalan Hatiari, Dusun Air Louw, Nusaniwe District, Ambon City. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews and documentation, with five teachers as the main participants. Data analysis was conducted based on Thomas Lickona's character education theory, which emphasizes three main components of character formation: moral knowing, moral feeling, and moral action. The results of the study indicate that teachers play an important role in shaping students' disciplinary character through modeling, positive reinforcement, behavior reinforcement, and consistent enforcement of rules. Teachers also create a conducive learning environment for character development through communicative and reflective interactions. This study concludes that active involvement and moral awareness of teachers are key factors in the success of character education in elementary schools. These findings can serve as a reference for the development of more systematic and applicable character education programs at the elementary school level.